2020
DOI: 10.1007/s11604-020-00956-y
|View full text |Cite|
|
Sign up to set email alerts
|

Ultra-high-resolution computed tomography can demonstrate alveolar collapse in novel coronavirus (COVID-19) pneumonia

Abstract: Purpose To review the chest computed tomography (CT) findings on the ultra-high-resolution CT (U-HRCT) in patients with the Novel coronavirus disease 2019 . Materials and MethodsIn February 2020, six consecutive patients with COVID-19 pneumonia (median age, 69 years) underwent U-HR CT imaging. U-HR-CT has a larger matrix size of 1024 × 1024 thinner slice thickness of 0.25 mm and can demonstrate terminal bronchioles in the normal lungs; as a result, Reid's secondary lobules and their abnormalities can be identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 15 publications
2
56
2
Order By: Relevance
“…1 ). In line with the previous study where different degrees of alveolar collapse were found in 6 COVID-19 patients ( Iwasawa et al, 2020 ), our findings indicate that the COVID-19 are generally accompanied by reduced volume of the lung and lung lobes, with increased density and mass. The pattern of CAP is similar with non-pneumonia subjects, except that the density of CAP patients is relatively larger.…”
supporting
confidence: 93%
“…1 ). In line with the previous study where different degrees of alveolar collapse were found in 6 COVID-19 patients ( Iwasawa et al, 2020 ), our findings indicate that the COVID-19 are generally accompanied by reduced volume of the lung and lung lobes, with increased density and mass. The pattern of CAP is similar with non-pneumonia subjects, except that the density of CAP patients is relatively larger.…”
supporting
confidence: 93%
“… Author Conclusion Fan L [13] Summarizes the CT imaging characteristics of COVID-19, clinical category, CT imaging performance of COVID-19 children, CT imaging difference between COVID-19 patients and other pulmonary inflammation patients. Iwasawa T [14] Ultra-high-resolution CT image can identify the terminal bronchiole in normal lungs. U-HR-CT can be used to detect abnormal lung volume reduction, which is essential for the early diagnosis and timely treatment of critical illness in COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, DL based-CAD systems that use medical images are recommended as another tool in the diagnosis and control of the novel coronavirus. Such CAD systems offer a quick and easy solution for medical diagnosis of COVID-19 (Iwasawa et al, 2020). Moreover, these CAD systems have the potential to deliver an accurate and fast second opinion, to help radiologists in giving an accurate diagnosis based on medical images (Ardakani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%